Composite brazing filler metal and method for brazing connection of Ag and Ni-Cr alloy
By using Ag-Cu-Zn-Sn+Ti composite brazing and vacuum brazing technology, the problems of debonding and low thermal conductivity of the binder in the traditional method of connecting Ni-Cr alloy to Ag are solved, and high strength and Good heat dissipation welding connection.
Patent Information
- Application Number
- CN202411683352.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-18
AI Technical Summary
In the traditional method of connecting Ni-Cr alloys and Ag, silicone grease binders are prone to debonding under high temperature environments and have low thermal conductivity, resulting in large interface thermal resistance, limiting the application field of electric heating elements.
Ag-Cu-Zn-Sn+Ti composite solder is prepared by ball mill mixing and drying. Combined with vacuum brazing technology, the heating and cooling rate are controlled to achieve efficient brazing connection between Ni-Cr alloy sheet and Ag sheet.
The connection strength and heat dissipation ability of Ni-Cr alloy and Ag sheet are improved. The obtained welded joint is flat and dense, free of cracks and cracks. The room temperature shear strength can reach 315MPa and has good corrosion resistance.
Smart Images

Figure CN119457568A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of brazing, in particular to a composite brazing material and a method for brazing Ag and Ni-Cr alloy. Background Art
[0002] Ni-Cr alloy has high resistivity and low temperature coefficient of resistance, high oxidation resistance and corrosion resistance, high high temperature strength, and good processing performance. It is often used as an electrothermal alloy and is widely used in aerospace, power electronics and other fields. With the rapid development of new energy vehicles, electronic packaging and other fields, higher requirements are also placed on the performance of corresponding power electronic devices. When electronic devices are working, current passes through semiconductor devices, which will convert part of the electrical energy into thermal energy, causing the internal temperature of the device to rise, affecting the efficiency of the device. It is necessary to conduct away the heat generated by the electronic device during operation in a timely manner. Ag has excellent thermal conductivity and is often used as a heat dissipation device in high-precision instruments. Connecting Ni-Cr electrothermal alloy with Ag can reduce the temperature of the lead-out end of the electrothermal alloy component, reduce power loss and facilitate the connection of the power cord, which has broad industrial application prospects.
[0003] The traditional method of connecting Ni-Cr alloy and Ag mainly uses silicone grease as an adhesive. However, silicone grease adhesive is easy to debond in high temperature environment, and the thermal conductivity of silicone grease is much lower than that of metal materials, which produces higher interfacial thermal resistance at the interface, greatly reducing the connection strength between Ni-Cr electric heating alloy and Ag and the heat dissipation capacity of the end, which greatly limits the application field of electric heating elements and cannot widely meet industrial needs.
[0004] Conventional solder is composed of metal elements such as Ag, Cu, and Sn. Since Ni-Cr alloy has high chemical stability and is not easy to react with solder, this chemical stability leads to poor wettability of solder on the surface of Ni-Cr alloy. In addition, the surface energy of Ni-Cr alloy is low, making it difficult for solder to spread on its surface. Summary of the invention
[0005] In view of this, the present invention provides a composite solder and a method for brazing Ag and Ni-Cr alloy, wherein Ag-Cu-Zn-Sn+Ti composite solder is used to achieve brazing connection of Ni-Cr alloy sheet and Ag sheet, and the composite solder has good wettability and filling ability to Ni-Cr alloy and Ag sheet.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] In the first aspect, the present invention discloses a composite solder, which is composed of 40-45% silver, 25-30% copper, 20-25% zinc, 2-3% tin, and 1-5% titanium in terms of mass percentage. The Ti content of 1%-5% is the optimal range obtained through experiments and theoretical analysis, which aims to balance the oxidation resistance, bonding strength and organizational characteristics, and improve the performance of the welded joint. Too high or too low Ti content will have a negative impact on the quality of the welded joint. Specifically, too high a Ti content will increase the melting point of the solder and increase the difficulty of welding, while too low a content will result in insufficient oxidation resistance. Too low a Ti content will not form an effective TiO2 protective layer, resulting in aggravated oxidation during high-temperature welding. Insufficient Ti content will lead to insufficient formation of intermetallic compounds, thereby reducing the bonding strength of the joint. Uneven organization: Too low a Ti content may result in uneven joint organization, affecting overall performance.
[0008] In a second aspect, the present invention discloses a method for preparing the above-mentioned composite solder, comprising the following steps:
[0009] (1) Weighing each component according to mass percentage, mixing silver, copper, zinc and tin, and ball milling the mixture for 2-2.5 hours to obtain a premix;
[0010] (2) adding titanium and an organic solvent to the premix, and continuing ball milling for 2-2.5 hours to obtain a viscous material;
[0011] (3) Drying the viscous material to obtain a composite solder.
[0012] As a further solution of the present invention: the ball ratio of the ball mill in steps (1) and (2) is 5:1.
[0013] In a third aspect, the present invention discloses a method for brazing Ag and Ni-Cr alloy using the composite brazing filler metal, comprising the following steps:
[0014] S1. Grind and clean the surfaces of the Ag sheet and the Ni-Cr alloy sheet thoroughly for later use;
[0015] S2, evenly laying the composite solder on the surface of the Ni-Cr alloy sheet, and then laying the Ag sheet on the composite solder to obtain a brazed structural part;
[0016] S3, placing the brazing structure into a vacuum brazing furnace for heating, taking it out after heating-keeping-cooling, and cooling it to room temperature.
[0017] As a further solution of the present invention: in step S3, the temperature is raised to 820-900°C at a rate of 5-10°C / min; the heat preservation time is 2-5min; the temperature is lowered to 400-450°C at a rate of 10-20°C / min.
[0018] During the heating process, the solder first undergoes a transition from a solid phase to a liquid phase. The melting point of Ag-Cu-Zn-Sn solder is lower than 900°C, so when the temperature reaches 820°C-900°C, the solder begins to melt and form liquid metal. As the temperature gradually increases, the diffusion rate of each element in the solder increases, which helps to form a uniform liquid phase. Controlling the heating rate can avoid thermal stress and phase change stress caused by excessive temperature, and reduce the risk of material deformation and cracking. At the same time, an appropriate heating rate helps to ensure that the solder is fully melted and promotes uniform distribution of elements.
[0019] During the insulation stage, the interface reaction between the brazing filler metal and the substrate (such as Ni-Cr alloy sheet and Ag sheet) begins to form an alloying layer or reaction product. This process is crucial to improving the bonding strength of the joint. When the temperature is kept at an appropriate level, the addition of Ti in the brazing filler metal can promote the mutual diffusion of Ti and the substrate, forming a Ti-based reaction layer, further enhancing the joint strength. Keeping the temperature at 820℃-900℃ for 2-5 minutes can ensure sufficient reaction time to achieve ideal interface reaction and alloying, and improve the mechanical properties of the connection. Too long an insulation time can cause overheating and damage to the material, while too low a temperature can lead to insufficient reaction.
[0020] During the cooling process, the liquid phase of the solder will gradually solidify, and the precipitation phase will form, affecting the final material properties. If the cooling rate is too fast, residual stress will be generated in the material, leading to changes in the microstructure, such as the generation of cracks. Therefore, controlling the cooling rate can reduce the temperature gradient inside the material, thereby reducing the generation of thermal stress and preventing the formation of cracks. Slow cooling helps promote the homogenization of crystals and the uniform distribution of precipitation phases, and improves the strength and toughness of the material. However, too slow a cooling rate will form coarse grains, so the cooling rate needs to be controlled within a specific range.
[0021] Proper temperature control can optimize the microstructure of the brazed joint and improve the bonding strength and reliability of the joint. This includes promoting uniform melting and diffusion in the heating stage, promoting effective interface reaction in the insulation stage, and reducing residual stress in the cooling stage, thereby ensuring the improvement of the final welding quality.
[0022] As a further solution of the present invention: in step S1, the composite solder is laid with a thickness of 60-150 μm.
[0023] As a further solution of the present invention: the Ni-Cr alloy sheet is composed of 70-80% nickel, 15-25% chromium and 2-5% iron in terms of mass percentage.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The invention discloses a method for connecting an Ag sheet and a Ni-Cr alloy sheet by using an Ag-Cu-Zn-Sn+Ti composite solder. The Ag-Cu-Zn-Sn low-temperature solder containing active element Ti is used. The brazing temperature is about 820°C, which is lower than the melting point of the Ag sheet base material. The Ti element is an active element and can react with most metals. The Ti element has good wettability and gap-filling ability for the Ni-Cr alloy and the Ag sheet. Meanwhile, according to the proportion of the composite solder, the heating rate and the cooling rate during brazing are controlled so that the obtained weld joint is flat and dense without defects such as cracks and fissures. According to tests, the room temperature shear strength of the joint can reach 315MPa, and the joint has good corrosion resistance. Therefore, the Ag-Cu-Zn-Sn+Ti composite low-temperature solder can effectively connect the Ni-Cr alloy sheet and the Ag sheet. The invention is mainly applied to the field of small-sized structural parts and components. The Ag sheet and the Ni-Cr alloy sheet are connected to obtain large-sized high-strength structural parts and components. The invention has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 is a SEM image of the connection interface between the Ni-Cr alloy and metal Ag in Example 2 of the present invention;
[0027] Figure 2 Schematic diagram of the brazing connection between the Ag sheet and the Ni-Cr alloy sheet. DETAILED DESCRIPTION
[0028] For ease of understanding of the present invention, the present invention will be described more fully below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.
[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0030] All materials in the following examples and comparative examples are commercially available conventional products. In addition, the "parts" described in the examples and comparative examples, unless otherwise specified, refer to parts by weight.
[0031] Any range described in the present invention includes the end value and any numerical value between the end values and any sub-range formed by the end value or any numerical value between the end values.
[0032] Preparation Example 1
[0033] (1) 47 parts of silver, 27 parts of copper, 22 parts of zinc, and 2.5 parts of tin powder were mixed and placed in a ball mill with a ball-to-material ratio of 5:1 and a ball milling time of 2 h to obtain a premix;
[0034] (2) adding 1.5 parts of titanium and 30 parts of anhydrous ethanol to the premix of step (1), and continuing ball milling for 2 hours, with a ball-to-material ratio of 5:1, to obtain a viscous material;
[0035] (3) The viscous material of step (2) is placed in an oven and dried at 40° C. to obtain a composite solder 1.
[0036] Example 1
[0037] Step 1: Use 800# sandpaper to polish the surface of Ni-Cr alloy sheet and Ag sheet, then put them into acetone solution for ultrasonic cleaning for 10 minutes to remove surface oil and impurities, and dry them for later use;
[0038] Step 2: evenly spread 1 on the surface of the Ni-Cr alloy sheet with a thickness of 60 μm, and use a stainless steel fixture to place the Ag sheet on the Ni-Cr alloy sheet covered with the composite solder 1 to assemble the equipment parts of the brazing structure;
[0039] Step 3: Place the equipment in step (2) in a vacuum brazing furnace and heat it. When the vacuum degree reaches 5×10 - 3 Pa, start the heating program, control the heating rate to 5℃ / min, heat to 820℃, keep warm for 2min, then control the cooling rate to 15℃ / min, cool to 400℃, and cool to room temperature with the furnace to obtain the brazing sample.
[0040] Preparation Example 2
[0041] (1) 46.5 parts of silver, 27 parts of copper, 22 parts of zinc, and 2.5 parts of tin powder were mixed and placed in a ball mill with a ball-to-material ratio of 5:1 and a ball milling time of 2 h to obtain a premix;
[0042] (2) adding 2 parts of titanium and 30 parts of anhydrous ethanol to the premix of step (1), and continuing ball milling for 2 hours, with a ball-to-material ratio of 5:1, to obtain a viscous material;
[0043] (3) The viscous material of step (2) is placed in an oven and dried at 40° C. to obtain composite solder 2.
[0044] Example 2
[0045] Step 1: Use 800# sandpaper to polish the surface of the Ni-Cr alloy sheet and the Ag sheet, and then put them into acetone solution for ultrasonic cleaning for 15 minutes to remove surface oil and impurities;
[0046] Step 2: evenly spread the composite solder 2 on the surface of the Ni-Cr alloy sheet with a thickness of 100 μm, and use a stainless steel fixture to place the Ag sheet on the Ni-Cr alloy sheet covered with the composite solder 2 to form a brazing structure equipment part;
[0047] Step 3: Place the equipment in step (2) in a vacuum brazing furnace and heat it. When the vacuum degree reaches 5×10 - 3 Pa, start the heating program, control the heating rate to 5℃ / min, heat to 840℃, keep warm for 5min, then control the cooling rate to 15℃ / min, cool to 400℃, and then cool to room temperature with the furnace to obtain the brazing sample.
[0048] Preparation Example 3
[0049] (1) 45.5 parts of silver, 27 parts of copper, 22 parts of zinc, and 2.5 parts of tin powder were mixed and placed in a ball mill with a ball-to-material ratio of 5:1 and a ball milling time of 2 h to obtain a premix;
[0050] (2) adding 3 parts of titanium and 30 parts of anhydrous ethanol to the premix of step (1), and continuing ball milling for 2 hours, with a ball-to-material ratio of 5:1, to obtain a viscous material;
[0051] (3) The viscous material of step (2) is placed in an oven and dried at 40° C. to obtain composite solder 3.
[0052] Example 3
[0053] Step 1: Use 800# sandpaper to polish the surface of the Ni-Cr alloy sheet and the Ag sheet, and then put them into acetone solution for ultrasonic cleaning for 25 minutes to remove surface oil and impurities;
[0054] Step 2: evenly spread the composite solder 3 on the surface of the Ni-Cr alloy sheet with a thickness of 120 μm, and use a designed stainless steel fixture to place the Ag sheet on the Ni-Cr alloy sheet covered with the composite solder 3 to form a brazing structure equipment part;
[0055] Step 3: Place the equipment in step (2) in a vacuum brazing furnace and heat it. When the vacuum degree reaches 5×10-3Pa, start the heating program, control the heating rate to 5℃ / min, heat to 850℃, keep warm for 6min, and then cool at a cooling rate of 15℃ / min. After cooling to 400℃, cool to room temperature with the furnace to obtain the brazing sample.
[0056] Preparation Example 4
[0057] (1) 44.5 parts of silver, 27 parts of copper, 22 parts of zinc, and 2.5 parts of tin powder were mixed and placed in a ball mill with a ball-to-material ratio of 5:1 and a ball milling time of 2 h to obtain a premix;
[0058] (2) adding 4 parts of titanium and 30 parts of anhydrous ethanol to the premix of step (1), and continuing ball milling for 2 hours, with a ball-to-material ratio of 5:1, to obtain a viscous material;
[0059] (3) The viscous material of step (2) is placed in an oven and dried at 40° C. to obtain a composite solder 4.
[0060] Example 4
[0061] Step 1: Use 800# sandpaper to polish the surface of the Ni-Cr alloy sheet and the Ag sheet, and then put them into acetone solution for ultrasonic cleaning for 30 minutes to remove surface oil and impurities;
[0062] Step 2: evenly spread the composite solder 4 on the surface of the Ni-Cr alloy sheet with a thickness of 130 μm, and use a stainless steel fixture to place the Ag sheet on the Ni-Cr alloy sheet covered with the composite solder 4 to form a brazing structure equipment part;
[0063] Step 3: Place the equipment in step (2) in a vacuum brazing furnace and heat it. When the vacuum degree reaches 5×10 - 3 Pa, start the heating program, control the heating rate to 5℃ / min, heat to 870℃, keep warm for 3min, then control the cooling rate to 15℃ / min, cool to 400℃, and then cool to room temperature with the furnace to obtain the brazing sample.
[0064] Preparation Example 5
[0065] (1) 43.5 parts of silver, 27 parts of copper, 22 parts of zinc, and 2.5 parts of tin powder were mixed and placed in a ball mill with a ball-to-material ratio of 5:1 and a ball milling time of 2 h to obtain a premix;
[0066] (2) adding 2.5 parts of titanium and 30 parts of anhydrous ethanol to the premix of step (1), and continuing ball milling for 2 hours, with a ball-to-material ratio of 5:1, to obtain a viscous material;
[0067] (3) The viscous material of step (2) is placed in an oven and dried at 40° C. to obtain a composite solder 5.
[0068] Example 5
[0069] Step 1: Use 800# sandpaper to polish the surface of the Ni-Cr alloy sheet and the Ag sheet, and then put them into acetone solution for ultrasonic cleaning for 40 minutes to remove surface oil and impurities;
[0070] Step 2: evenly spread the composite solder 5 on the surface of the Ni-Cr alloy sheet with a thickness of 150 μm, and use a stainless steel fixture to place the Ag sheet on the Ni-Cr alloy sheet covered with the composite solder 5 to form a brazing structure equipment part;
[0071] Step 3: Place the equipment in step (2) in a vacuum brazing furnace and heat it. When the vacuum degree reaches 5×10 - 3 Pa, start the heating program, control the heating rate to 5℃ / min, heat to 900℃, keep warm for 3min, then control the cooling rate to 15℃ / min, cool to 400℃, and then cool to room temperature with the furnace to obtain the brazing sample.
[0072] Comparative Example 1
[0073] (1) 46.5 parts of silver, 27 parts of copper, 22 parts of zinc, and 2.5 parts of tin powder were mixed and placed in a ball mill with a ball-to-material ratio of 5:1 and a ball milling time of 2 h to obtain a premix;
[0074] (2) adding 0.5 parts of titanium and 30 parts of anhydrous ethanol to the premix of step (1), and continuing ball milling for 2 hours, with a ball-to-material ratio of 5:1, to obtain a viscous material;
[0075] (3) The viscous material of step (2) is placed in an oven and dried at 40° C. to obtain a composite solder 6.
[0076] (4) The surfaces of the Ni-Cr alloy sheet and the Ag sheet were polished with 800# sandpaper, and then ultrasonically cleaned in an acetone solution for 15 min to remove surface oil and impurities;
[0077] (5) The composite solder 6 is evenly spread on the surface of the Ni-Cr alloy sheet with a thickness of 100 μm, and the Ag sheet is placed on the Ni-Cr alloy sheet with the composite solder 2 using a stainless steel fixture to form a brazing structure equipment part;
[0078] (6) Place the equipment in step (5) in a vacuum brazing furnace and heat until the vacuum reaches 5×10 -3 Pa, start the heating program, control the heating rate to 5℃ / min, heat to 840℃, keep warm for 5min, then control the cooling rate to 15℃ / min, cool to 400℃, and then cool to room temperature with the furnace to obtain the brazing sample.
[0079] Comparative Example 2
[0080] (1) 46.5 parts of silver, 27 parts of copper, 22 parts of zinc, and 2.5 parts of tin powder were mixed and placed in a ball mill with a ball-to-material ratio of 5:1 and a ball milling time of 2 h to obtain a premix;
[0081] (2) adding 7 parts of titanium and 30 parts of anhydrous ethanol to the premix of step (1), and continuing ball milling for 2 hours, with a ball-to-material ratio of 5:1, to obtain a viscous material;
[0082] (3) The viscous material of step (2) is placed in an oven and dried at 40° C. to obtain a composite solder 7.
[0083] (4) The surfaces of the Ni-Cr alloy sheet and the Ag sheet were polished with 800# sandpaper, and then ultrasonically cleaned in an acetone solution for 15 min to remove surface oil and impurities;
[0084] (5) The composite solder 7 is evenly spread on the surface of the Ni-Cr alloy sheet with a thickness of 100 μm, and the Ag sheet is placed on the Ni-Cr alloy sheet with the composite solder 2 using a stainless steel fixture to form a brazing structure equipment part;
[0085] (6) Place the equipment parts in step (5) in a vacuum brazing furnace for heating. When the vacuum degree reaches 5×10-3Pa, start the heating program, control the heating rate to 5℃ / min, heat to 840℃, keep warm for 5min, then control the cooling rate to 15℃ / min, cool to 400℃, and then cool to room temperature with the furnace to obtain the brazing sample.
[0086] Comparative Example 3
[0087] (1) 46.5 parts of silver, 27 parts of copper, 22 parts of zinc, and 2.5 parts of tin powder were mixed and placed in a ball mill with a ball-to-material ratio of 5:1 and a ball milling time of 2 h to obtain a premix;
[0088] (2) adding 3 parts of titanium and 30 parts of anhydrous ethanol to the premix of step (1), and continuing ball milling for 2 hours, with a ball-to-material ratio of 5:1, to obtain a viscous material;
[0089] (3) The viscous material of step (2) is placed in an oven and dried at 40° C. to obtain a composite solder 6.
[0090] (4) The surfaces of the Ni-Cr alloy sheet and the Ag sheet were polished with 800# sandpaper, and then ultrasonically cleaned in an acetone solution for 15 min to remove surface oil and impurities;
[0091] (5) The composite solder 6 is evenly spread on the surface of the Ni-Cr alloy sheet with a thickness of 100 μm, and the Ag sheet is placed on the Ni-Cr alloy sheet with the composite solder 2 using a stainless steel fixture to form a brazing structure equipment part;
[0092] (6) Place the equipment in step (5) in a vacuum brazing furnace and heat until the vacuum reaches 5×10 -3Pa, start the heating program, control the heating rate to 15℃ / min, heat to 840℃, keep warm for 5min, then control the cooling rate to 10℃ / min, cool to 400℃, and then cool to room temperature with the furnace to obtain the brazing sample.
[0093] Comparative Example 4
[0094] (1) 46.5 parts of silver, 27 parts of copper, 22 parts of zinc, and 2.5 parts of tin powder were mixed and placed in a ball mill with a ball-to-material ratio of 5:1 and a ball milling time of 2 h to obtain a premix;
[0095] (2) adding 3 parts of titanium and 30 parts of anhydrous ethanol to the premix of step (1), and continuing ball milling for 2 hours, with a ball-to-material ratio of 5:1, to obtain a viscous material;
[0096] (3) The viscous material of step (2) is placed in an oven and dried at 40° C. to obtain a composite solder 6.
[0097] (4) The surfaces of the Ni-Cr alloy sheet and the Ag sheet were polished with 800# sandpaper, and then ultrasonically cleaned in an acetone solution for 15 min to remove surface oil and impurities;
[0098] (5) The composite solder 6 is evenly spread on the surface of the Ni-Cr alloy sheet with a thickness of 100 μm, and the Ag sheet is placed on the Ni-Cr alloy sheet with the composite solder 2 using a stainless steel fixture to form a brazing structure equipment part;
[0099] (6) Place the equipment in step (5) in a vacuum brazing furnace and heat until the vacuum reaches 5×10 -3 Pa, start the heating program, control the heating rate to 5℃ / min, heat to 840℃, keep warm for 5min, then control the cooling rate to 10℃ / min, cool to 400℃, and then cool to room temperature with the furnace to obtain the brazing sample.
[0100] The shear strength of the brazing samples obtained in Examples 1-3 and Comparative Examples 1-2 was tested using a universal testing machine, and the testing standard was based on GB / T 11363-2008 “Test method for strength of brazed joints”.
[0101] The test results are shown in Table 1.
[0102] Table 1
[0103]
[0104] It can be seen from the shear strength of the samples in Example 2 and Comparative Examples 1 and 2 that too high or too low a titanium content will have a negative impact on the brazing shear strength. It can be seen from Example 2 and Comparative Examples 3 and 4 that the heating rate is usually controlled within a certain range to reduce thermal stress and prevent deformation, and the cooling rate also needs to be controlled within a certain range to avoid affecting the metallographic structure and generating excessive thermal stress and cracks.
[0105] Although this specification is described according to implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
[0106] Therefore, the above description is only a preferred embodiment of the present application and is not intended to limit the scope of implementation of the present application; that is, all equivalent changes made according to the scope of the claims of the present application are within the protection scope of the claims of the present application.
Claims
1. A composite solder, characterized in that: It is composed of 40-45% silver, 25-30% copper, 20-25% zinc, 2-3% tin and 1-5% titanium according to mass percentage.
2. The method for preparing the composite solder according to claim 1, characterized in that: The following steps are involved: (1) Weighing each component according to mass percentage, mixing silver, copper, zinc and tin, and ball milling the mixture for 2-2.5 hours to obtain a premix; (2) adding titanium and an organic solvent to the premix, and continuing ball milling for 2-2.5 hours to obtain a viscous material; (3) Drying the viscous material to obtain a composite solder.
3. The preparation method according to claim 2, characterized in that: The ball ratio of the ball mill in steps (1) and (2) is 5:
1.
4. A method for brazing Ag and Ni-Cr alloy using the composite brazing filler metal as claimed in claim 1, characterized in that: The following steps are involved: S1. Grind and clean the surfaces of the Ag sheet and the Ni-Cr alloy sheet thoroughly for later use; S2, evenly laying the composite solder on the surface of the Ni-Cr alloy sheet, and then laying the Ag sheet on the composite solder to obtain a brazed structural part; S3, placing the brazing structure into a vacuum brazing furnace for heating, taking it out after heating-keeping-cooling, and cooling it to room temperature.
5. The method according to claim 4, characterized in that In step S3, the temperature is raised to 820-900°C at a rate of 5-10°C / min; the temperature is kept at a temperature for 2-5min; and the temperature is lowered to 400-450°C at a rate of 10-20°C / min.
6. The method according to claim 4, characterized in that In step S2, the composite solder is laid with a thickness of 60-150 μm.
7. The method according to claim 4, characterized in that The Ni-Cr alloy sheet is composed of 70-80% nickel, 15-25% chromium and 2-5% iron in terms of mass percentage.